Smoking, alcohol and diet in relation to risk of pancreatic cancer in China: a prospective study of 0.5 million people - Pang, Y; Holmes, M; Guo, Y; Yang, L; Bian, Z; Chen, Y; Iona, A; Millwood, I; Bragg, F; Chen, J; Li, L; Kartsonaki, C; et al. (Wiley, 2017)
In China the incidence of pancreatic cancer (PC) has increased in recent decades. However, little is known about the relevance to PC risk of lifestyle and behavioural factors such as smoking, alcohol drinking, and diet. The China Kadoorie Biobank prospective study recruited 512,891 adults (210,222 men, 302,669 women) aged 30-79 (mean 52) years from 10 diverse areas during 2004-08. During ~8 years of follow-up, 688 incident cases of PC were recorded among those who had no prior history of cancer at baseline. Cox regression yielded adjusted hazard ratios (HR) for PC associated with smoking, alcohol and selected dietary factors. Overall, 74% of men were ever-regular smokers and 33% of men drank at least weekly, compared with only 3% and 2% of women, respectively. Among men, current regular smoking was associated with an adjusted HR of 1.25 (95% CI 1.08-1.44) for PC, with greater excess risk in urban than rural areas (1.46 [1.19-1.79] vs 1.04 [0.86-1.26]). Heavy, but not light to moderate, alcohol drinking (i.e. ≥420 g/week) was associated with significant excess risk (1.69 [1.21-2.37]), again more extreme in urban than rural areas (1.93 [1.29-2.87] vs 1.35 [0.74-2.48]). Overall, regular consumption of certain foodstuffs was associated with PC risk, with adjusted daily vs never/rare consumption HRs of 0.66 (0.56-0.79) for fresh fruit and 1.16 (1.01-1.33) for red meat. In China, smoking and heavy alcohol drinking were independent risk factors for PC in men. Lower fresh fruit and higher red meat consumption were also associated with higher risk of PC.